Dissecting the Discourse of Social Licence to Operate - Sinner J; Newton M; Farrelly T (Massey University)
The term “social licence to operate”, or SLO, has increasingly featured in public discussion about commercial operations in the marine environment. As part of the Sustainable Seas National Challenge, we are studying how this term is being used in New Zealand and its implications for industry-community relations.